Pengaruh Pengelolaan Keuangan dan Status Perkawinan Terhadap Kesejahteraan Keuangan Keluarga di Desa Karangjaya - Ayu Nuradilah; Ujang Suherman; Rengga Madya Pranata (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the influence of financial management and marital status on family financial well-being in Karangjaya Village, Tirtamulya District, Karawang Regency. This study uses a descriptive quantitative approach with data collection through questionnaires from 79 respondents selected using the simple random sampling method. Data analysis was carried out using multiple linear regression. The results of the study indicate that financial management has a significant influence on family financial well-being, which reflects the importance of budget planning, spending control, and saving and investing habits in improving financial well-being. Marital status also has a significant influence, where relationship stability and cooperation in the household also encourage more rational and planned financial decisions. Simultaneously, both variables contribute 28.8% to the variation in family financial well-being. The implication of this study is the importance of structured financial literacy education and fostering marriage readiness as part of efforts to improve the economic welfare of the community, especially in rural areas.